Self-regulated learning levels among elementary education students: Thorndike's law of readiness analysis in hybrid learning - Ardiansyah, Roy; Nafisah, Ainun; Rahmadian, Rizqi Karisma; Candrarini, Mujiati (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2025)
Students with strong self-regulated learning (SRL) skills can effectively regulate their motivation and learning strategies to achieve academic success. However, many students face significant challenges in their academic journey, especially experiencing stress from heavy coursework loads during hybrid learning, which often causes delays and disrupts their academic progress, resulting in students' SRL not being as expected. This study aims to assess the self-regulated learning levels of elementary school teacher education (PGSD) students in hybrid learning environments from the perspective of Thorndike's Law of Readiness.   Using a quantitative survey approach, data were collected from 108 undergraduate students of elementary school teacher education at Universitas Sebelas Maret using questionnaires. This study employed content validity through expert judgment and Cronbach Alpha for reliability testing. Data analysis was conducted using descriptive statistics.  The results indicate varying levels of self-regulated learning among undergraduate students of elementary school teacher education: 36.1% exhibited very high SRL, 40.7% high, 21.3% moderate, and 1.9% low. Analysis through Thorndike's Law of Readiness indicates that most students are well-prepared to handle their responsibilities in hybrid learning environments.   This study contributes to a deeper understanding of SRL in hybrid settings, helping students enhance self-regulation and enabling them to better manage, stay motivated, and achieve their academic goals.